Rethinking Higher Education in Nepal Through the Perspective of PMPD - Dangal, Megh R.; Karki, Isha (State, Society and Development: PMPD Perspectives, 2025)
This paper explores the critical need for transformative reforms within Nepal’s higher education system to effectively address challenges related to quality, alignment with human capital development, innovation, and employability. As the country undergoes a demographic transition and aspirations for higher education rise, the current system is constrained by an outdated curriculum, inadequate infrastructure, and a lack of meaningful collaboration between academic institutions and industry. These issues contribute to brain drain, as many Nepalese youth seek educational and professional opportunities abroad, highlighting the urgent need for competitive local alternatives. To identify the various factors influencing transformative reform in Nepal’s higher education sector, this study employs a mixed-method approach that foregrounds the narratives of students in higher education, supported by quantitative data. The participants in the study are students from colleges and universities in Kathmandu. The paper argues for a paradigm shift toward a hybrid educational model that balances intrinsic human development with the pragmatic demands of labor market readiness. Recommended strategies for reform include the modernization of curricula, the integration of emerging technologies such as information technology and artificial intelligence, and the development of strong partnerships between academia and industry. By addressing these multifaceted challenges through collaborative efforts involving diverse stakeholders and targeted policy interventions, Nepal can work toward building an inclusive, innovation-driven higher education system that fosters human capital development, reduces brain drain, and contributes to sustainable economic growth.